Penerapan Acceptance and Commitment Therapi (ACT) untuk Meningkatkan Keberfungsian Penyandang Disabilitas Fisik di Sentra Budi Perkasa Palembang - Putri Prezelia; Suryati Suryati; Neni Noviza (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: The purpose of this study was to determine the functioning of persons with physical disabilities in the Budi Perkasa Center in Palembang and to determine the application of Acceptance and Commitment Therapy (ACT) to improve the functioning of persons with physical disabilities in the Budi Perkasa Center in Palembang. This research is a descriptive research, the data collection tools used are: interviews, observation, and documentation. The subjects of this study were two beneficiaries (PM). The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of this study are: 1) the functioning of persons with physical disabilities in the Budi Perkasa Sentra Palembang is still at a low level where several aspects make beneficiaries (PM) unable to carry out their social functions. The aspect of functioning consists of individuals being able to carry out their roles well, individuals having responsibility towards others and individuals obtaining self-satisfaction. 2) implementation of Acceptance and Commitment Therapy (ACT) to improve the functioning of persons with physical disabilities at the Budi Perkasa Palembang Center through 3 stages namely the initial stage, the middle stage and the final stage. The result of applying Acceptance and Commitment Therapy (ACT) to the two beneficiaries (PM) is that they are able to improve their social functioning by accepting current conditions and building a commitment to find, train, maintain and develop new behaviors. KEYWORDS: functioning of persons with physical disabilities, Acceptance and Commitment Therapy (ACT)